2019
DOI: 10.1103/physrevb.99.014304
|View full text |Cite
|
Sign up to set email alerts
|

Ellipticity dependence transition induced by dynamical Bloch oscillations

Abstract: The dependence of high-harmonic generation (HHG) on laser ellipticity is investigated using a modified ZnO model. In the driving of relatively weak field, we reproduce qualitatively the ellipticity dependence as observed in the HHG experiment of wurtzite ZnO. When increasing the field strength, the HHG shows an anomalous ellipticity dependence, similar to that observed experimentally in the single-crystal MgO. With the help of a semiclassical analysis, it is found that the key mechanism inducing the change of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 52 publications
2
38
0
3
Order By: Relevance
“…Nonlinear periodic intraband currents can be driven by strong laser field motion of electrons and holes in the CB and the VB, respectively, resulting in the generation of higher order harmonics of the fundamental laser frequency. Furthermore, higher harmonics can be generated via interband recombination of electrons and holes, leading to emission of quanta with energies determined by the electron-hole momentum at the moment of recombination plus the bandgap energy ( Figure 1 a, lower panel) [ 23 ]. Thus, this mechanism would be responsible for harmonics with energies of quanta larger than the bandgap.…”
Section: Pl and Hhg Emission From Zno Thin Films And Bulkmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonlinear periodic intraband currents can be driven by strong laser field motion of electrons and holes in the CB and the VB, respectively, resulting in the generation of higher order harmonics of the fundamental laser frequency. Furthermore, higher harmonics can be generated via interband recombination of electrons and holes, leading to emission of quanta with energies determined by the electron-hole momentum at the moment of recombination plus the bandgap energy ( Figure 1 a, lower panel) [ 23 ]. Thus, this mechanism would be responsible for harmonics with energies of quanta larger than the bandgap.…”
Section: Pl and Hhg Emission From Zno Thin Films And Bulkmentioning
confidence: 99%
“…Figure 3 b shows the fit parameters and , determined from the fitting procedure of the experimental results measured in the ZnO bulk (red) and thin film (blue) samples as a function of the harmonic order n . Furthermore, fit parameter values—calculated using theoretical models by Liu et al (black) [ 22 ] and Zhang et al (green) [ 23 ]—using a Gaussian fit function are shown in the upper panel of Figure 3 b. Both theoretical simulations are based on the density matrix equation and the results for the above band gap higher harmonics are interpreted in a frame of the semiclassical saddle-point analysis.…”
Section: Ellipticity Dependence Of Hhgmentioning
confidence: 99%
See 1 more Smart Citation
“…electron correlation. We predict that eh-PER should be ubiquitous in a large range of extreme nonlinear phenomena of current interest, such as HHG with elliptical drivers [1,3,4,8,27,35,56,57] and systems with large Berry curvatures [58], as well as high-order sideband generation [59][60][61][62]. The identification of eh-PER and its effect on the harmonic emission profiles, as well as the formulation of the ERM, provides new insights into the HHG process in solids and could potentially stimulate new experiments.…”
mentioning
confidence: 93%
“…Two main theoretical approaches to study HHG in solids include (i) the time-dependent Schrödinger equation (TDSE) for individual Bloch electrons with specific k values [25][26][27][28][29][30][31][32][33][34][35], and (ii) many-electron approaches such as the semiconductor Bloch equations (SBEs) [36][37][38][39][40][41][42][43][44][45][46] and the time-dependent density-functional theory (TDDFT) [23,[47][48][49][50][51][52][53][54][55][56]. In Ref.…”
Section: Introductionmentioning
confidence: 99%